The challenge of BRIC multinationals - Tulder, Rob van; Verbeke, Alain; Carneiro, Jorge, active 2016; Gonzalez-Perez, Maria-Alejandra (Progress in international business research, 2016)
This PIBR volume examines a number of idiosyncratic elements in the internationalization strategies of BRIC MNEs and, in particular, in their relationship with home country policies: 1.The theoretical challenge: do we need different or more specific theories of EMNEs to assess the phenomenon of BRIC multinationals? 2.The empirical challenge: what marks the changing position of BRIC countries in the world economy? 3.The managerial challenge: with the coming of age of a new breed of multinationals, what distinguishes BRIC multinationals from other (emerging market) multinationals? 4.The policy making challenge: what impact have MNEs from BRIC countries had on their domestic economy?